Movement observation specifies motor programs activated by the action observed objective - Lago, Angel; Fernandez-del-Olmo, Miguel (Neuroscience letters, 2011)
► We study the muscle specificity of the “motor resonance” mechanism during action observation. ► Observation of a static effector in front of an object produces a goal-based specific activation. ► Effector–object interaction produces a muscle specification of the activated motor program. There are human cortical areas that fire both when a person executes an action and when he observes someone performing a similar action. The observer activates a motor program that resembles the observed action. However, it is not known whether the motor program activated via action observation is muscle specific. In this study, using simple pulse transcraneal magnetic stimulation (TMS) applied over the primary motor cortex (M1), we investigated whether the Mirror System activates a muscle specific motor program, or codes the observed action in terms of its goal. The results showed that when subjects observed a static effector in front of an object, cortical excitability was enhanced even in muscles not involved in the observed movement, but that are able to achieve the goal of the action. When there was an effector–object interaction the motor program activated via action observation is muscle specific. These results suggest that when subjects observe an object related action there is an activation of a motor program based on the observed action goal, that is transformed into a muscle specific program when the subject shows an effector–object interaction.